Murder and mamon - Manansala, Mia P. (Manansala, Mia P. Tita Rosie's kitchen mystery., 2023)
"The next riveting mystery in the Tita Rosie's Kitchen series by Mia P. Manansala, Agatha Award-winning author of Arsenic and Adobo. Lila Macapagal's godmothers April, Mae, and June--aka the Calendar Crew--are celebrating the opening of their latest joint business venture, a chain of laundromats. However, what should've been a joyous occasion quickly turns into a tragedy when they discover the body of Ninang April's niece, recently arrived from the Philippines, spinning around inside one of the machines. With Ninang April falling apart from grief and little progress from the Shady Palms Police Department, it's up to Lila and her network to find justice for the young woman. The Calendar Crew have stuck their noses into everybody's business for years, but now it seems the tables are turned as Lila must pry into the Calendar Crew's lives to figure out who has a vendetta against the extremely opinionated yet loving aunties and stop them before they strike again"--